PENGARUH AMBIGUITAS PERAN DAN MOTIVASI TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU, BATAM, DAN MEDAN) - Safitri, Devi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This research aims to analyze and gets empirical prove of role ambiguity andmotivation to auditor performance. Respondens in this research are auditors whowork on public accounting firm at Pekanbaru, Batam and Medan. There 145 auditorsfrom 29 accounting firm were visited. The method of determining the sample is byusing purposive sampling method. This research is a quantitative model with dataanalysis methods include validity, reliability, normality test, classical assumptions:multicollinearity, heteroscedasticity, and multiple regression, test determinantcoefficient and hypothesis test: t test by using SPSS version 17.00 as the softwarefor processing data. The results of this research indicate that role ambiguity has asignificant effect to auditor performance and motivations have a significant effect onthe performance of auditors.Keyword: role ambiguity, motivation and auditor performance